Sosialisasi Menggunakan Haksuara Dan Don't Abstain Pada Pemilu 2024 Untuk Generasi Muda Di Desa Bongohulawa - Melo, Ramla Hartini; S. Niode, Alim; Lasulika, Cindy; Zakaria, Muhammad Rejki (Universitas Negeri Gorontalo, 2024)
People who do not exercise their right to vote while voting are called abstainers. When it comes to the 2024 elections, the company needs to understand the negative consequences of not participating and develop countermeasures. In Indonesia, the process of strengthening political awareness and government actions to preserve Pancasila and the 1945 Constitution is known as